Entrepreneurship and competitiveness dynamics in Latin America - Zoltán J. Ács; José Ernesto Amorós (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This study analyses the relationship between entrepreneurial dynamics and the level of competitiveness in Latin American countries. Based on a stage of economic development model we demonstrate that Latin American countries under the model followed different paths related to competitiveness. These different paths can explain the effect of specific competitiveness conditions on entrepreneurial dynamics in Latin America.
Keywords: L26; M13; O54; 330; Entrepreneurship; competitiveness; development; Latin America; Unternehmer; Internationaler Wettbewerb; Entwicklung; Lateinamerika